2008
DOI: 10.1074/jbc.m804279200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Tautomycin Biosynthetic Gene Cluster from Streptomyces spiroverticillatus Unveiling New Insights into Dialkylmaleic Anhydride and Polyketide Biosynthesis

Abstract: Tautomycin (TTM) is a highly potent and specific protein phosphatase inhibitor isolated from Streptomyces spiroverticillatus. The biological activity of TTM makes it an important lead for drug discovery, whereas its spiroketal-containing polyketide chain and rare dialkylmaleic anhydride moiety draw attention to novel biosynthetic chemistries responsible for its production. To elucidate the biosynthetic machinery associated with these novel molecular features, the ttm biosynthetic gene cluster from S. spirovert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 54 publications
5
48
0
1
Order By: Relevance
“…24 As for the alkylmaleic anhydride substituent, one may deduce a biosynthetic scheme from the tautomycin pathway. 25 Osada and colleagues 25 suggested that the dialkylmaleic anhydride moiety is biosynthesized through an aldol condensation of methylmalonylCoA and a-ketoglutarate derived from the Krebs cycle. In analogy, a plausible route toward the monoalkylmaleic anhydride side chain of 6 would involve an aldol condensation of acetyl-CoA with the C-5 unit derived from a-keto glutarate, followed by dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…24 As for the alkylmaleic anhydride substituent, one may deduce a biosynthetic scheme from the tautomycin pathway. 25 Osada and colleagues 25 suggested that the dialkylmaleic anhydride moiety is biosynthesized through an aldol condensation of methylmalonylCoA and a-ketoglutarate derived from the Krebs cycle. In analogy, a plausible route toward the monoalkylmaleic anhydride side chain of 6 would involve an aldol condensation of acetyl-CoA with the C-5 unit derived from a-keto glutarate, followed by dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…Spiroketal rings are found in tautomycin, avermectins, and spirandienes (10,14,18). It have been postulated that the spiroketal ring formation could proceed spontaneously by dual nucleophilic attack on the carbonyl carbon atom (C-14) by the two hydroxyl groups at C-10 and C-18 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon skeleton of spirotoamides A(1) and B(2) is likely assembled by a type I polyketide synthase, which might catalyze the loading of the acetate unit and the condensation of four malonylCoAs, four methylmalonyl-CoAs and one ethylmalonyl-CoA. Based on the knowledge of tautomycin 20 and avermectin 21 biosyntheses, the presence of a dihydroxyl ketone precursor was expected in the formation of the spiroacetal structure (Figure 4). We recently analyzed the biosynthesis of reveromycin A and identified RevJ responsible for the stereospecific spiroacetal formation from the dihydroxyl ketone precursor.…”
Section: Resultsmentioning
confidence: 99%